2007
DOI: 10.2478/s11532-007-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Addition of TiO2 nanowires in different polymorphs for dye-sensitized solar cells

Abstract: TiO 2 (B) and TiO 2 anatase nanowires were prepared at 150• C for 120 h by a hydrothermal method followed by calcination in air at 400• C for 2 h and at 700 • C for 2 h for TiO 2 (B) and TiO 2 anatase, respectively. Although dye-sensitized solar cells (DSC) with fully nanowire electrodes showed a rather low light-to-electricity conversion efficiency of 1.33 % for TiO 2 (B) and 2.42% for TiO 2 anatase, 10 wt % nanowire-dispersed electrodes in a P-25 TiO 2 -nanoparticle matrix demonstrated improved efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…In a separate experiment, addition of 10 %-nanowire to a commercial nanopowder (namely, route (i) as described in the introduction part) showed highest efficiency among 0-100 % nanowire compositions [46], which is in good agreement with this study. In addition, in situ thermal fragmentation (described as route (iv)) concurrently proceeded after route (iii), and as a result, approximately 10 % nanowires remained in the final DSC device.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a separate experiment, addition of 10 %-nanowire to a commercial nanopowder (namely, route (i) as described in the introduction part) showed highest efficiency among 0-100 % nanowire compositions [46], which is in good agreement with this study. In addition, in situ thermal fragmentation (described as route (iv)) concurrently proceeded after route (iii), and as a result, approximately 10 % nanowires remained in the final DSC device.…”
Section: Discussionsupporting
confidence: 79%
“…Since, neither long-time hydrothermal treatment nor mixing process with nanopowder is required for this process, it is in principle cost-effective. However, microstructural control and optimization are required, and these will be the subject of our forthcoming papers [46,47]. attachment crystal growth" of nanoparticles by SATM.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific surface area of nanorods is lower than nanoparticles, the photogenerated electron can directly move along the 1-D ordered structure to conducting glass and reduced the possible loss of photoelectron and increase the performance of the cell. On the controversy, the previous work suggested that addition of nanorods into nanoparticles system may decrease the total specific surface area [4][5]6,13]. Therefore, proper content of nanorods supplementary into nanoparticles may completely increase the performance, notable the PCE, of DSSCs.…”
Section: Resultsmentioning
confidence: 99%
“…These include ordered nanostructured materials, especially, one dimensional (1-D) structured materials [3][4]. In these materials, greater photovoltaic performances may be gained through the development of anode materials with ordered structure effect in the enhancement of electron transport [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the random contacts of TiO 2 nanoparticles at grain boundaries lead to trapping and recombination of electrons and holes, which limits the efficiency of the DSSCs. 5), 6) Substantial efforts have been made to improve well-organized photoelectrode materials. These include ordered nanostructured materials, especially, one dimensional (1-D) structured materials.…”
Section: )2)mentioning
confidence: 99%